RANCANG BANGUN SMOKE GENERATOR DENGAN ALIRAN ASAP SECARA KONSTAN UNTUK MEDIA PEMBELAJARAN DI LABORATORIUM AERODINAMIKA - Matondang, Pahottua; Wailanduw, A. Grummy (Universitas Negeri Surabaya, 2021)
Students who carry out practicum at the Aerodynamics Laboratory of Mechanical Engineering, State University of Surabaya have a smoke generator that is still simple, where the tool still has shortcomings in producing thick and constant smoke. The design of this tool uses the Research and Development (R&D) method with the analysis carried out covering the design of the tool, the heater used and the material. Trials of several heating devices and materials that have been carried out such as water heaters using liquid paraffin and dry ice. The second experiment was using a hairdryer using liquid paraffin, VG glycerin and VG+PG glycerin, the third experiment using flat nickelin wire with liquid paraffin, VG glycerin and VG+PG glycerin and the fourth experiment using coiled nickelin wire using liquid paraffin, VG glycerin and glycerin. VG+PG. Experiments on heating devices and materials were carried out by dripping and also partially soaking, except for heating water with dry ice by adding hot air to dry ice. From the experiments that have been carried out, the maximum heating device in producing as soon as possible is using a coil of nickelin wire with liquid paraffin. The results of the development and engineering of the research tool decided to use 3 coils of nickelin wire with a length of 120 mm, a diameter of 10 mm with a resistance per nickelin of 3.5 Ohm. For the power supply, the adapter uses an AC input of 220V DC output of 24V 10A and uses liquid paraffin as a liquid to be evaporated, because it does not cause corrosion of tools or wind tunnels. This tool works by evaporating liquid paraffin that is submerged in a coil of nickelin wire with a horizontal hanging position. It takes 3-5 minutes to get production fast which is good. From the smoke generator test results, this tool can be used for 10 minutes per rake in the wind tunnel in the data collection process.